Predictors of Late Mortality in D‐Transposition of the Great Arteries After Atrial Switch Repair: Systematic Review and Meta‐Analysis. Issue 21 (5th November 2019) - Venkatesh, Prashanth; Evans, Arthur T.; Maw, Anna M.; Pashun, Raymond A.; Patel, Agam; Kim, Luke; Feldman, Dmitriy; Minutello, Robert; Wong, S. Chiu; Stribling, Judy C.; LaPar, Damian; Holzer, Ralf; et al.
Abstract : Background: Existing data on predictors of late mortality and prevention of sudden cardiac death after atrial switch repair surgery for D‐transposition of the great arteries (D‐TGA) are heterogeneous and limited by statistical power. Methods and Results: We conducted a systematic review and meta‐analysis of 29 observational studies, comprising 5035 patients, that reported mortality after atrial switch repair with a minimum follow‐up of 10 years. We also examined 4 additional studies comprising 105 patients who reported rates of implantable cardioverter‐defibrillator therapy in this population. Average survival dropped to 65% at 40 years after atrial switch repair, with sudden cardiac death accounting for 45% of all reported deaths. Mortality was significantly lower in cohorts that were more recent and operated on younger patients. Patient‐level risk factors for late mortality were history of supraventricular tachycardia (odds ratio [OR] 3.8, 95% CI 1.4–10.7), Mustard procedure compared with Senning (OR 2.9, 95% CI 1.9–4.5) and complex D‐TGA compared with simple D‐TGA (OR 4.4, 95% CI 2.2–8.8). Significant risk factors for sudden cardiac death were history of supraventricular tachycardia (OR 4.7, 95% CI 2.2–9.8), Mustard procedure (OR 2.2, 95% CI 1.1–4.1), and complex D‐TGA (OR 5.7, 95% CI 1.8–18.0). Out of a total 124 implantable cardioverter‐defibrillator discharges over 330 patient‐years in patients with implantable cardioverter‐defibrillators for primary prevention, only 8% were appropriate. Conclusions: Patient‐level risk of both mortality and sudden cardiac death after atrial switch repair are significantly increased by history of supraventricular tachycardia, Mustard procedure, and complex D‐TGA. This knowledge may help refine current selection practices for primary prevention implantable cardioverter‐defibrillator implantation, given disproportionately high rates of inappropriate discharges.